Polarização da cárie em município sem água fluoretada Polarization of dental caries in a Brazilian city without fluoridated water - Luciana Cardoso; Cassiano Rösing; Paulo Kramer; Carolina Covolo da Costa; Luiz Cesar da Costa Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
A maior exposição da população brasileira ao flúor da água e dos dentifrícios fluoretados tem sido apontada como principal responsável pela redução da prevalência de cárie. Dessa forma, o objetivo do presente trabalho foi avaliar a distribuição da cárie em uma população de 437 crianças, com idades entre 6 e 12 anos, residentes em uma cidade sem sistema de fluoretação da água de abastecimento e sem programa odontológico preventivo, podendo, com isso, orientar futuras ações de saúde com melhor desempenho no que diz respeito à relação custo-efetividade. Para tanto, foi realizado exame clínico em todas as crianças para avaliação dos índices CPO-S e ceo-s, o que representa o número de superfícies dentárias cariadas, perdidas ou com extração indicada e restauradas. A análise de freqüência acumulada da doença em relação à freqüência acumulada da população mostrou que 37% das crianças concentravam 70% da doença, com um ceo-s + CPO-S médio de 28,6. Essa distribuição evidencia o fenômeno da polarização, no qual uma pequena parcela da população concentra a maior parte da doença e das necessidades de tratamento. Increased overall exposure of the Brazilian population to fluoridated water and fluoridated dentifrices has been identified as the main factor in the reduction of caries prevalence. Thus, the objective of the present study was to evaluate the distribution of caries in a group of 437 children ranging from 6 to 12 years of age, residing in a city without a water supply fluoridation system and without a preventive dentistry program, with the aim of orienting future health measures towards improved cost-effectiveness. Clinical examination was performed on all the children, focusing on the indices defs (decayed, extracted, and filled primary dentition surfaces) and DMFS (decayed, missing, and filled permanent dentition surfaces), representing the number of dental surfaces that were either decayed, missing or with extraction indicated, or restored. Analysis of accumulated disease frequency in relation to the population showed that 37% of the children presented 70% of all the tooth disease, with a mean defs + DMFS of 28.6. This distribution demonstrates the phenomenon of polarization, in which most of the disease and treatment needs are concentrated in a small portion of the population.